Seasonal Length-weight Relationship of Puntius terio (Hamilton, 1822) in West Bengal, India - Angsuman Chanda; Godhuli Sit; Arun Jana (Aquatic Sciences and Engineering)
The present study aims to analyse the association among length, weight, condition factor, and relative condition factor of Puntius terio (Hamilton,1822), with a focus on seasonal change. The results indicate that the species did not strictly follow the anticipated cube law and had allometric development in all seasons. The length-weight relationship value (b) ranged from 2.14 to 3.21; the condition factor varied between 0.62 and 2.65, and the relative condition factor ranged from 0.61 to 2.98 for P. terio in the study area. The average values of ‘b’ were highest during the monsoon, but the condition factor (K) was highest during the winter. The seasonal association between length, weight, condition factor, and relative condition factor was significant (P<0.05) according to the Post Hoc test. The current research will support the development of sustainable management strategies for P. terio in its habitats by fishery managers.